2022
DOI: 10.1002/smll.202201045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Interfacial Modification for Stable Zn Anode Based on a Thin Separator

Abstract: The interface plays a pivotal role in stabilizing metal anode. Extensive studies have been made but systematic research is lacking. In this study, preliminary studies are conducted to explore the prime conditions of interfacial modification to approach the practical requirements. Critical factors including reaction kinetics, transport rate, and modulus are identified to affect the Zn anode morphology significantly. The fundamental principle to enhance the Zn anode stability is systematically studied using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In general, the Zn ions in LE tend to 2D diffuse along the Zn anode surface to find the energetically favorable sites (tip sites) for diminishing the surface energy, and then the Zn 2+ ions aggregate together and further are reduced into dendrites. 13,56 As for the SPS–Zn system, the current density remains stable after 60 s, suggesting that the initial nucleation and transverse diffusion processes occurred in a relatively short time followed by steady and constant three-dimensional (3D) diffusion. The obtained results indicated that SPS–Zn can constrain the 2D surface lateral movement and facilitate the absorbed Zn 2+ ions on the electrode to locally reduce into metallic Zn (as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the Zn ions in LE tend to 2D diffuse along the Zn anode surface to find the energetically favorable sites (tip sites) for diminishing the surface energy, and then the Zn 2+ ions aggregate together and further are reduced into dendrites. 13,56 As for the SPS–Zn system, the current density remains stable after 60 s, suggesting that the initial nucleation and transverse diffusion processes occurred in a relatively short time followed by steady and constant three-dimensional (3D) diffusion. The obtained results indicated that SPS–Zn can constrain the 2D surface lateral movement and facilitate the absorbed Zn 2+ ions on the electrode to locally reduce into metallic Zn (as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] However, these conventional materials cannot fully satisfy the requirements of a high performance separator, including low thickness, high porosity, sufficient mechanical strength, high electrolyte wettability, and low cost. [ 10,15 ] Meanwhile, these materials can hardly induce the uniform distribution and deposition of Zn 2+ , resulting in low Coulombic efficiencies, poor cyclability, and premature device failure. [ 13b ]…”
Section: Introductionmentioning
confidence: 99%
“…Li et al. proposed a facile and distinct interfacial engineering strategy to immobilize persimmon branch carbon (PBC) material on a cellulose filter (CF) paper separator [55] . The PBC material with graded pore structure, uniformly distributed carbon sites, and abundant N and O functional groups is designed as an effective ion transport modulator PBC@CF separator with the dual functions of facilitating ion transfer and inhibiting dendrite growth.…”
Section: Improved Strategies For Separatorsmentioning
confidence: 99%